Os relevos quartzíticos do sector de Soutelo - Arrancada do Vouga - Águeda (NW de Portugal) : enquadramento estratigráfico e morfotectónico - Gomes, António Alberto (2008)
This work aims at presenting a stratigraphic and morphotectonic regional framework of the quartzite relief of the Soutelo - Arrancada do Vouga - Águeda structural domain (Iberian Massif, NW Portugal). The Armorican quartzite discontinuous outcrops take the form of a narrow N-S strip, with a 1 km wide, of Lower Palaeozoic age, which is included in a major crustal-scale strike-slip zone, the so-called Porto-Coimbra-Tomar shear zone. This crystalline basement bears a very characteristic and ubiquitous tectonostratigraphy. The morphotectonic and geological surveys led us to newly describe and mapping the quartzite relief structure to the North of Águeda village, until the left margin of Vouga River. The large-scale relief is strongly associated with the existence of scarps along inherited regional fault and shear zones. These results suggest that relief development in this region was mainly controlled by tectonics through fault zones reactivation.